VIDEOFLUOROSCOPIC EVALUATION OF THE IMPACT OF CAPSULE SIZE AND SUBJECT’S AGE AND GENDER ON CAPSULE SWALLOWING - GUTIERRES, Laís Flavia de Souza; MONTALDI, Marina Rodrigues; NASCIMENTO, Weslania Viviane; DANTAS, Roberto Oliveira (Arquivos de gastroenterologia, 2024)
ABSTRACT Background: People recurrently have difficulties swallowing solid medications, which can be associated with the size of the medication and the age and gender of individuals. Objective: To evaluate the impact of capsule size and adults’ age and gender on oral and pharyngeal capsule transit during capsule swallows. Methods: Videofluoroscopy was used to measure capsule oral and pharyngeal transit during swallows in 49 healthy individuals (17 men and 32 women), with a mean age of 46 years (ranging from 23 to 88 years). Smaller capsules were filled with 0.50 mL of barium sulfate, and larger capsules were filled with 0.95 mL of barium sulfate; the volume of liquid ingested with the capsules was also quantified in each ingestion. The measurements included the oral preparation time, oral transit time, swallowing reaction time, time to laryngeal vestibule closure, laryngeal vestibule closure duration, pharyngeal transit time, and upper esophageal sphincter opening duration. Results: The capsule size did not influence either the oral or pharyngeal transit time. Increased liquid volume was ingested with larger capsules and by people older than 40 years. The oral transit time was shorter in older adults (60-88 years), and the time to laryngeal vestibule closure was longer in women. Conclusion: The size of large capsules did not make a difference in oral or pharyngeal transit when compared with smaller capsules. The capsule size and the participant’s age influenced the volume of liquid ingested - larger capsules and older individuals required a larger volume. The capsule oral transit was faster in individuals older than 60 years. RESUMO Contexto: Algumas pessoas apresentam recorrentemente dificuldades para engolir medicamentos sólidos, o que pode estar associado ao tamanho do medicamento, à idade e ao gênero dos indivíduos. Objetivo: Avaliar, em adultos, o impacto do tamanho da cápsula, da idade e do gênero no trânsito oral e faríngeo de cápsulas. Métodos: Videofluoroscopia foi utilizada para medir o trânsito oral e faríngeo de cápsulas em 49 indivíduos saudáveis (17 homens e 32 mulheres), com idade média de 46 anos (limites de 23 e 88 anos). Cápsulas menores foram preenchidas com 0,50 mL e cápsulas maiores foram preenchidas com 0,95 mL de sulfato de bário; o volume de líquido ingerido com as cápsulas foi quantificado em cada ingestão. Foram medidos o tempo de preparo oral, tempo de trânsito oral, tempo de reação da deglutição, tempo para fechamento do vestíbulo laríngeo, tempo de fechamento do vestíbulo laríngeo, tempo de trânsito faríngeo e tempo de abertura do esfíncter superior do esôfago. Resultados: O tamanho da cápsula não influenciou o tempo de trânsito oral ou faríngeo. Mais líquido foi ingerido com cápsulas maiores e por pessoas com mais de 40 anos. O tempo de trânsito oral foi menor em idosos (60-88 anos) e o tempo de fechamento do vestíbulo laríngeo foi maior em mulheres. Conclusão: O tamanho da cápsula não influenciou o trânsito oral e faríngeo, porém houve maior volume de líquido ingerido com a cápsula maior e nos mais idosos. O trânsito oral da cápsula foi mais rápido em indivíduos com mais de 60 anos.